Paradigma Baru Madrasah dalam Implementasi Kebijakan Kurikulum 2013 - Andi Prastowo (Jurnal Pendidikan Islam, 2014)
Policy implementation is a process applying the decision of policy which usually early with a compilation of the program, a project of till to activities for resolving a problem of becoming policy agenda. Ministry of the Religion Republic Of Indonesia also has plans for the implementation of the policy of Curriculum 2013 in all ladder of the madrasah, including one of them at the ladder of madrasah ibtidaiyah, the start year 2014. This implementation has of implication to change various education aspect in madrasah like Standard Process, Standard Content, Standard Interest Grad, Standard Assessment, and also at Textbook Lesson. This paradigm becomes someone's reference or institution in taking decisions and policies to act.